Pengaruh Media Math Playground Terhadap Hasil Belajar Matematika Siswa Kelas V - Detri Yani; Dendi Tri Suarno (LPPPI Publishing, 2026)
The rapid development of digital technology has transformed learning practices, including the integration of game-based learning media in mathematics instruction. Mathematics is often perceived as an abstract and challenging subject for elementary school students, resulting in low engagement and suboptimal learning outcomes. This study aimed to examine the effect of Math Playground media on the mathematics learning outcomes of fifth-grade students at SDN 12 Nusa Pandau. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The sample consisted of 17 fifth-grade students selected through saturated sampling. Data were collected through multiple-choice pretest and posttest instruments that had been validated and tested for reliability. Data analysis included the Shapiro–Wilk normality test and paired sample t-test. The results showed a significant improvement in students’ learning outcomes after the implementation of Math Playground. The mean pretest score increased from 65 to 85 in the posttest. The Shapiro–Wilk test indicated normal data distribution (Sig. 0.549 and 0.239 > 0.05). The paired sample t-test revealed a significance value of 0.001 (< 0.05), indicating a statistically significant difference between pretest and posttest scores. These findings suggest that the use of interactive game-based learning media can enhance students’ understanding and engagement in mathematics learning.